Comparison of Synthetic and Biologic Mesh in Ventral Hernia Repair Using Components Separation Technique. Issue 6 (June 2016) - Sandvall, Brinkley K.; Suver, Daniel W.; Said, Hakim K.; Mathes, David W.; Neligan, Peter C.; Dellinger, E. Patchen; Louie, Otway
Abstract : Abstract: Ventral hernia repair (VHR) for large abdominal wall defects is challenging. Prior research established that the use of mesh is superior to suture closure alone and that component separation is an effective technique to combat loss of abdominal domain. Studies comparing component separation technique (CST) outcomes utilizing synthetic versus biologic mesh are limited. A retrospective review was conducted of 72 consecutive patients who underwent VHR with CST between 2006 and 2010 at our institution. Surgeon preference and the presence of contamination guided whether synthetic mesh (27 patients) or biologic mesh (45 patients) was used. Mean follow-up interval for all comers was 13.9 months and similar in both groups ( P > 0.05). Degree of contamination and severity of premorbid medical conditions were significantly higher in the biologic mesh group, as reflected in the higher Ventral Hernia Working Group (VHWG) score (2.04 versus 2.86). Clinical outcomes, as measured by both minor and major complication rates and recurrence rates, were not significantly different. Minor complication rates were 26% in the synthetic group and 37% in the biologic group and major complication rates 15% in the synthetic group and 22% in the biologic group. There was 1 recurrence (4%) in the synthetic mesh group versus 5 (11%) in the biologic mesh group. Multivariable analysis for major complications revealed no significant difference for either synthetic or biologic mesh while controlling for other variables. Subset analysis of uncontaminated cases revealed recurrence rates of 4% in the synthetic mesh group and 6% in the biologic mesh group. VHR using CST and either synthetic mesh or biologic mesh resulted in low recurrence rates with similar overall complication profiles, despite the higher average VHWG grading score in the biologic mesh group. Our results support the VHWG recommendation for biologic mesh utilization in higher VHWG grade patients. In VHWG grade 2 patients, our clinical outcomes were similar, supporting the use of either type of mesh.